New record of Teleogryllus (Macroteleogryllus) derelictus Gorochov, 1985 from India - Monaal; Gulati, Harsh; Jaiswara, Ranjana (Zootaxa, 2025)
Genus Teleogryllus (Orthoptera: Gryllidae) includes 55 species worldwide, with 13 previously reported from India. This study revises the taxonomy of T. derelictus Gorochov, 1985, providing new data on its acoustics, habitat and morphology; it also includes the first description of female genitalia. We confirm its range expansion to Assam, India, increasing the total Teleogryllus species in the country to 14.